P21-Activated kinase 3 promotes cancer stem cell phenotypes through activating the Akt-GSK3β-β-catenin signaling pathway in pancreatic cancer cells. (1st August 2019) - Wu, Hsing-Yu; Yang, Ming-Chen; Ding, Li-Yun; Chen, Ching S.; Chu, Po-Chen
Abstract: Relative to several other p21-activated kinase (PAK) family members, the role of PAK3 in regulating cancer cell functions remains unclear. Our study obtained evidence that PAK3 regulates the Akt-GSK3β-β-catenin signaling by acting as Ser 473 -Akt kinase in several pancreatic cancer cell lines. Specifically, knockdown of PAK3 or overexpression of dominant-negative PAK3 inhibited the phosphorylation of Ser 473 -Akt and GSK3β, resulting in the proteasomal degradation of β-catenin. Conversely, overexpression of PAK3 led to activation of Akt signaling and increased β-catenin expression. These changes, however, were not noted with the silencing and/or overexpression of PAK1, PAK2, or PAK4, which underlies the impetus of PAK3 as a key effector in governing malignant phenotypes in these pancreatic cancer cells, including cancer stem cell (CSC) expansion. Accordingly, PAK3 depletion effectively suppresses tumorsphere formation, ALDH activity, and the expression of CSC surface markers. Moreover, we used a stable knockdown clone of AsPC-1 cells to demonstrate the in vivo efficacy of PAK3 inhibition in suppressing tumorigenesis and xenograft tumor growth. Together, these findings suggest the potential role of PAK3 as a target for pancreatic cancer therapy, which warrants further investigations. Highlights: PAK3 regulates β-catenin stability via Akt/GSK3β signaling. PAK3 is involved in the regulation of CSC-like properties of pancreatic cancer cells. PAK3 represents a therapeutic target in pancreatic cancer.